2006
DOI: 10.1681/asn.2006030209
|View full text |Cite
|
Sign up to set email alerts
|

Renal Damage after Myocardial Infarction Is Prevented by Renin-Angiotensin-Aldosterone-System Intervention

Abstract: Recently, it was shown that myocardial infarction aggravates preexistent mild renal damage that is elicited by unilateral nephrectomy in rats. The mechanism behind this cardiorenal interaction likely involves the renin-angiotensin-aldosteronesystem and/or vasoactive peptides that are metabolized by neutral endopeptidase (NEP). The renoprotective effect of angiotensin-converting enzyme inhibition (ACEi) as well as combined ACE/NEP inhibition with a vasopeptidase inhibitor (VPI) was investigated in the same mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…The pathophysiology in cardiorenal syndrome is poorly understood and likely involves interrelated concepts such as low cardiac output, increased venous congestion and renal venous pressure, neurohormonal and inflammatory activation, and local changes [2,19]. In good agreement with other observations [1,8,9], the present study has shown that common renal damage after MI could be significantly prevented by RAS intervention, such as with the use of losartan. Furthermore, increased inflammatory cell infiltration and fibrosis within the kidneys occurring post-MI heart failure has also been demonstrated by our previous study [6] and the other study [10].…”
Section: Discussionsupporting
confidence: 90%
“…The pathophysiology in cardiorenal syndrome is poorly understood and likely involves interrelated concepts such as low cardiac output, increased venous congestion and renal venous pressure, neurohormonal and inflammatory activation, and local changes [2,19]. In good agreement with other observations [1,8,9], the present study has shown that common renal damage after MI could be significantly prevented by RAS intervention, such as with the use of losartan. Furthermore, increased inflammatory cell infiltration and fibrosis within the kidneys occurring post-MI heart failure has also been demonstrated by our previous study [6] and the other study [10].…”
Section: Discussionsupporting
confidence: 90%
“…Here, we have proposed a concept that ties our results together with those of previous studies 56, 57 . Chronic cardiac volume overload leads to SNS activation, resulting in augmentation of intrarenal RAS and NADPH oxidase-dependent ROS production.…”
Section: Discussionmentioning
confidence: 53%
“…Subsequently, based on results obtained using an ACE inhibitor, they suggested that the RAS was involved in the pathogenesis of the progressive renal injury (54). In that study, however, the ACE inhibitor caused a dramatic decrease in blood pressure and an improvement in cardiac parameters.…”
mentioning
confidence: 96%